2006
DOI: 10.1271/bbb.70.821
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Genetically Modified Soybeans Using a Combination of a Capillary-Type Real-Time PCR System and a Plasmid Reference Standard

Abstract: Because the labeling of grains and feed- and foodstuffs is mandatory if the genetically modified organism (GMO) content exceeds a certain level of approved genetically modified varieties in many countries, there is a need for a rapid and useful method of GMO quantification in food samples. In this study, a rapid detection system was developed for Roundup Ready Soybean (RRS) quantification using a combination of a capillary-type real-time PCR system, a LightCycler real-time PCR system, and plasmid DNA as the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
(33 reference statements)
1
9
0
2
Order By: Relevance
“…The results clearly showed that the neomycin-and the puromycin-resistance genes could be quantitatively detected in the presence of genomic DNA extracted from beef samples, suggesting that the detection method is capable of being used to detect genomic DNAs from PRNP Ϫ/Ϫ cattle. Many real-time PCR detection methods based on fluorescence detection, such as TaqMan ® chemistry, have been developed to identify and quantify GM maize, 2-7) GM soybeans, [2][3][4][5]8,9) and GM varieties of other agricultural commodities 7) and to detect pork, beef, chicken, mutton, and horse in foods. 10) This model experiment in which standard plasmids were spiked into genomic DNA from a beef sample and were detected is thought to be reasonable and acceptable, because plasmid DNA markers containing cloned transgenic sequences have been used for genetically modified organism analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The results clearly showed that the neomycin-and the puromycin-resistance genes could be quantitatively detected in the presence of genomic DNA extracted from beef samples, suggesting that the detection method is capable of being used to detect genomic DNAs from PRNP Ϫ/Ϫ cattle. Many real-time PCR detection methods based on fluorescence detection, such as TaqMan ® chemistry, have been developed to identify and quantify GM maize, 2-7) GM soybeans, [2][3][4][5]8,9) and GM varieties of other agricultural commodities 7) and to detect pork, beef, chicken, mutton, and horse in foods. 10) This model experiment in which standard plasmids were spiked into genomic DNA from a beef sample and were detected is thought to be reasonable and acceptable, because plasmid DNA markers containing cloned transgenic sequences have been used for genetically modified organism analysis.…”
Section: Discussionmentioning
confidence: 99%
“…최근 정확한 GMO 의 정량분석을 위해서 real-time PCR이 이용되고 있으며, 정량 표준물질로 주로 내재유전자 및 도입유전자의 단편 을 포함한 plasmid을 사용하고 있다. 표준 plasmid의 이용은 목표 단편들에 대하여 정확한 농도로 표준용액을 조제할 수 있기 때문에 이로부터 GMO 시료의 농도를 용이하게 산출할 수 있는 장점이 있다 (Kuribara et al 2002;Toyota et al 2006;Zhang and Guo 2011). 따라서 Agb0101 벼의 정량 분석용 pRBECrR을 제작하였고, 이의 목적하는 내재유전 자 및 도입유전자의 단편들이 벡터 내에 삽입되어 있는 지 염기서열 분석을 수행한 결과, 예상한 염기서열과 정 확하게 일치하는 237 bp의 단편을 확인 하였다 (Fig.…”
Section: Real-time Pcr 검정을 위한 표준 Plasmid 제조unclassified
“…한편, 각 국가에서 는 GMO의 안전한 유통관리를 위해서 비의도적 혼입치 를 설정하여 표시제를 실시하고 있어 정량적인 분석법이 개발되고 있다. Real-time PCR분석법은 목적유전자의 PCR 증폭산물(amplicon)을 plasmid로 제작하여 표준물질로 하 고, 형광 probe를 이용함으로써 보다 정확한 GMO의 혼입 율을 확인할 수 있어 정밀분석을 가능케 하였다 (Kuribara et al 2002;Shindo et al 2002;Rho et al 2004;Toyota et al 2006). 국내에서는 살충성 유전자, mcryIAc1를 벼에 형질전환 하여 해충저항성 GM벼로 개발하였고 ), 최 근 GM작물의 실용화를 위해서 이벤트 Agb0101에 대한 식품 및 환경위해성평가 연구를 수행하였다.…”
unclassified
“…Many real-time polymerase chain reaction (PCR) detection methods based on fluorescence detection, such as TaqMan ® chemistry, have been widely developed to identify and quantify GM maize, [4][5][6][7][8][9] GM soybeans, [4][5][6][7]10,11) and GM varieties of other agricultural commodities. 9) Similar methods have also been used to detect pork, beef, chicken, mutton, and horseflesh in foods.…”
mentioning
confidence: 99%